1993
DOI: 10.3109/07853899309147318
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: Prenatal Influenza and Autoimmunity

Abstract: The schizophrenic syndrome may represent a stereotyped response by the developing brain to various insults, including micro-organisms. We review studies that have examined the association between schizophrenia and infectious agents, and examine the current evidence for the hypothesis that exposure to influenza during fetal life increases the risk of later schizophrenia. A prenatal autoimmune basis for some cases of schizophrenia is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 64 publications
0
19
1
1
Order By: Relevance
“…This is similar to the finding of hippocampal pyramidal cell disarray reported in human schizophrenia post-mortem studies [138][139][140] . Because the influenza virus or influenza virus antibodies have not been detected in the fetal brain, it has been hypothesized that the maternal immune response alone is sufficient to generate schizophrenia-like behavioural findings in the offspring 136,[141][142][143][144][145] . At the neurotransmitter level, dysfunctions in the dopaminergic and glutamatergic system have been reported, especially in the medial prefrontal cortex and the nucleus accumbens in offspring from mothers subjected to immune challenge 123 .…”
Section: Maternal Immune Activationmentioning
confidence: 99%
“…This is similar to the finding of hippocampal pyramidal cell disarray reported in human schizophrenia post-mortem studies [138][139][140] . Because the influenza virus or influenza virus antibodies have not been detected in the fetal brain, it has been hypothesized that the maternal immune response alone is sufficient to generate schizophrenia-like behavioural findings in the offspring 136,[141][142][143][144][145] . At the neurotransmitter level, dysfunctions in the dopaminergic and glutamatergic system have been reported, especially in the medial prefrontal cortex and the nucleus accumbens in offspring from mothers subjected to immune challenge 123 .…”
Section: Maternal Immune Activationmentioning
confidence: 99%
“…Other factors associated with increased schizophrenic births include famine during pregnancy, 63,64 Rh factor incompatibility, 65 and autoimmunity due to infectious agents. 66 A number of animal models are currently in use to study schizophrenia and identify potential new therapies (reviewed by Carpenter and Koenig 7 ). Our laboratory has studied the effects of prenatal human influenza viral infection on day 9 of pregnancy in BALB/c and C57BL/6 mice and their offspring.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Since viral infections are more common in winter, the disturbance of the intrauterine environment by maternal viral infection was supposed to explain the excess of winter births in schizophrenia, restoring an old hypothesis on the viral origin of insanity [44,45]. A slim majority of studies effectively reported an association between maternal exposition to influenza or other viral infections (namely polio, herpes, CMV, rubella) and subsequent diagnosis of schizophrenia in the offspring [24,[46][47][48][49][50].…”
Section: Perinatal Complications and Schizophreniamentioning
confidence: 97%